Label-Free Electrochemical Cell-Based Biosensor for Toxicity Assay of Water-Soluble Form of Phosphatidylcholine - Veronica V. Pronina; Lyubov V. Kostryukova; Sergey V. Ivanov; Elena G. Tichonova; Alexander I. Archakov; Victoria V. Shumyantseva (Biomedicines)
Background/Objectives: Our study brings a new method to properly evaluating drug efficacy at the non-invasive in vitro level. Methods: In this work, the electrochemical mediator-free and reagent-free analysis of cell lines based on the registration of electrochemical profiles of membrane proteins was developed. We studied the specificity of cell lines Wi-38 and HepG2 and the toxic effects of drugs on cell-on-electrode systems. Results: A linear dependence of the peak current on the concentration of cells applied to the electrode in the range from 1 × 105 to 6 × 105 cells/electrode was registered (R2 0.932 for Wi-38 and R2 0.912 for HepG2). The water-soluble form of phosphatidylcholine (wPC) nanoparticles recommended for atherosclerosis treatment and prevention of cardiovascular diseases did not show a toxic effect on the human fibroblast cells, Wi-38, or the human hepatocellular carcinoma cells, HepG2, at sufficiently high concentrations (such as 0.1–1 mg/mL). The antitumor drug doxorubicin, at concentrations of 3 and 10 μg/mL, showed a pronounced toxic effect on the tested cell lines, where the percentage of living cells was 50–55%. Conclusions: A comparative analysis of the cytotoxicity of wPC (0.1–1 mg/mL) and doxorubicin (3–10 μg/mL) on the cell lines Wi-38 and HepG2 using the MTT test and electrochemical approach for the registration of cells showed their clear adequacy.